Internet deployment of DPM-based IP traceback - Belenky, Andrey (Array, 2008)
In this article, we introduce the Internet deployment guidelines for Deterministic Packet Marking (DPM) - a novel IP traceback method. Unlike other packet marking schemes, DPM cannot be deployed sporadically on the Internet. Therefore, in order to perform the traceback, a structured way of deployment is needed. Related to topology and deployment issues, discussion comparing the features of other full path schemes and ingress packet filtering to those of DPM is also presented